(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the use of supraclavicular artery flap in head and neck reconstruction in terms of its reliability, clinical applications, and functional & aesthetic outcome. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the PIBC, Nishtar Medical University, Multan.It was completed in 18 months from June 2016 to Dec 2017. Materials and Methods: This study included 30 patients requiring soft tissue reconstruction in the head and neck region. Survival of supraclavicular artery flap, functional & aesthetic outcome, and donor site appearance were studied. Results: All flaps survived except for a distal 10 % necrosis seen in two cases. The functional and aesthetic outcomes were excellent with an acceptable donor site appearance. The areas reconstructed included neck, chin, cheek, jawline. Conclusion: The ideal flap to resurface head and neck defects has yet to be found. In our experience, the supraclavicular artery flap is one of the reconstructive techniques of choice for medium to large defects of the head and neck region. It is a reliable, thin and pliant fasciocutaneous flap, and expands significantly postoperatively.